Childhood Trauma, Peer Pressure, Social Media Usage, and Delinquent Career Choice among Youths in Ibadan, Nigeria - Ijiola, Timothy Olakunle; Asiyanbi, Mutiat; Ibrahim, Rashidat Omowumi (NIU Journal of Social Sciences, 2025)
This study investigated the relationships between childhood trauma, peer pressure, social media usage, and delinquent career choice among youths aged 15 to 24 years in Ibadan, Nigeria. A purposive sample of 200 participants was drawn from correctional centres, rehabilitation homes, and selected secondary schools to examine the psychosocial factors influencing vocational deviance. Using Pearson correlation and multiple regression analyses, the study found significant positive associations among childhood trauma, peer pressure, social media usage, and delinquent career orientation. Peer pressure emerged as the strongest predictor, followed by childhood trauma, while social media usage showed a smaller yet significant effect. The combined model explained 41.2% of the variance in delinquent career choice, highlighting the complex interplay of individual and social influences on youth behaviour. These findings underscore the need for integrated intervention programmes that address trauma, peer dynamics, and digital contexts to effectively mitigate delinquent pathways. The study also highlights implications for trauma-informed care and social skills training in rehabilitation and educational settings. Limitations related to sampling methods and cross-sectional design are acknowledged, with recommendations for longitudinal research and broader population samples to deepen understanding of these relationships. This research contributes to the growing literature on multifactorial determinants of youth delinquency in the Nigerian context, offering valuable insights for policymakers, educators, and mental health practitioners. Keywords: Childhood Trauma, Peer Pressure, Social Media Usage, Delinquent Career Choice